Women’s Participation in Agro-biodiversity Management: A Case Study of Kaski District - Acharya, R. (NPI Journal of Science and Technology, 2024)
The management of agro-biodiversity is integral to developing resilient and sustainable agricultural systems capable of addressing existing challenges. An investigation was carried out in Kaski district of Nepal during 2022 to explore the women’s participation in agro-biodiversity management. Pretested semi-structured questionnaire was employed to gather primary data from 100 farm households. Further, Focus Group Discussion (FGD) and Key Informant Interview (KII) was used to gather primary data. Mean, frequency and other measures were used to present the findings. Results revealed that women play major role in collection and preservation of Non-Timber Forest products (NTFPs) in comparison to men. Involvement of women in drying, storage, marketing and value addition was also high in comparison to men. Women farmers’ role in seed selection is predominant. Farmers are conserving traditional and exotic species of fodders, vegetables crops, and diversity on spices, cereals, oilseeds and legumes. From the above findings, it is suggested that the government and other development agencies should tailor policies and programs through the participation of women farmers for sustainability of conservation efforts. Moreover, involvement of stakeholders should be ensured in the implementation at the community level.